Korelasi antara Nilai Pendidikan Agama Islam dengan Perilaku Keagamaan Siswa Kelas V SD Negeri 02 Krandon Kecamatan Kesesi Kabupaten Pekalongan Tahun Pelajaran 2015/2016 - Inafa Atina (2021111380) (Prodi S-1 Pendidikan Agama Islam Jurusan Tarbiyah STAIN Pekalongan, 2016)
Mostly students at State Elementary School 02 Krandon got Islamic education subject scores which exceeded the criteria of minimal completeness. In terms of behavior, the students were categorized as well behaved students. It could be observed when the students met teachers; the students were not reluctant to greet their teachers. Besides, the students were accustomed to talk honestly and politely. They were educated to respect each other with their friends, teachers, parents, and local societies. The research problem in this study was how was the correlation between Islamic education subject scores and religious behaviors of students grade 5 at State Elementary School 02 Krandon, Kesesi Sub-district, Pekalongan District 2015/2016? The objective of this study was to describe the correlation between Islamic education subject scores and religious behaviors of students grade 5 at State Elementary School 02 Krandon, Kesesi Sub-district, Pekalongan District 2015/2016. The theoretical significance of this study was expected to be capable of being an input for the scientific development to those who would like to use this study further against the similar objects uncovered in the study. The practical significance of this study was to give information to the teachers at State Elementary School 02 Krandon, Kesesi Sub-district, Pekalongan District 2015/2016, especially to improve the quality of education as an attempt to improve the quality graduates. This study was field research; meanwhile the approach used was quantitative. The methods of data collection were questionnaire, observation, interview, and documentation. Whereas, in analyzing data the writer used descriptive statistic with correlation formula of product moment. The result showed that the average scores of Islamic education subject of students grade 5 at State Elementary School 02 Krandon were as high as 81, so that it was included in a good category viewed from students’ scores on the report books. Religious behaviors of students grade 5 were included in a good category, this could be proven with the average scores of questionnaire about religious behaviors of students grade 5 State Elementary School 02 Krandon, Kesesi Sub-district, Pekalongan District 2015/2016 (variable Y) as high as 101 in the interval 100-104 which was included in a good category. The result of this study showed that there was no significant correlation between Islamic education subject scores and religious behaviors of students grade 5 at State Elementary School 02 Krandon, Kesesi Sub-district, Pekalongan District 2015/2016.